The Effect of Self-Potential on Employment Prospects of FTIK IAIN Lhokseumawe Students - Siti Nurmawaddah Hasibuan; Nurasiah Nurasiah; Zulkhairi Zulkhairi (Jurnal Manajemen dan Ilmu Administrasi, 2026)
Abst This study aims to analyze the effect of self-potential on the job prospects of FTIK IAIN Lhokseumawe students in the context of human resource development. Self-potential is understood as an individual's internal capacity, which includes self-confidence, motivation, personal skills, adaptability, and work readiness, which play an important role in increasing the competitiveness of college graduates in the workforce. This study uses a quantitative approach with an associative research type. The research population consists of 70 FTIK IAIN Lhokseumawe graduates who have entered the workforce, all of whom were sampled using total sampling techniques. Data were collected using a structured questionnaire based on a Likert scale and analyzed using simple linear regression. The results show that self-potential has a positive and significant effect on students' job prospects. This finding confirms that self-potential is a strategic factor in human resource management and development, especially during the transition stage from education to the workforce. The novelty of this study lies in the positioning of self-potential as the main internal variable that independently influences students' job prospects in the context of Islamic religious universities.The implications of this study indicate that universities need to integrate self-development into their student management policies and programs in order to improve the employability and competitiveness of graduates.racts should be written in Indonesian using Times New Roman font size 11 with single spacing. The length should range from 150 to 250 words and presented in one paragraph. The abstract should summarize the main aspects of the study, including the purpose, methods, findings, novelty, and implications. The abstract should clearly demonstrate the contribution of the study to advancing knowledge in the field of psychology.